Biochar Derived from Post-Adsorbent for Immobilizing Cu and Cd in Sediment: The Effect on Heavy Metal Species and the Microbial Community Composition - Qinju Sun; Shaohua Lin; Guohua Liu; Pingping Li (Toxics, 2023)
Many biomass wastes or their modified forms have been investigated as heavy metal adsorbents. However, less emphasis has been placed on post-adsorbent management or possible further utilization. In this study, biochar (BC) derived from modified bamboo adsorbent after the adsorption of Cu from an aqueous solution was used for the in situ remediation of lake sediment contaminated with Cd and Cu. The results indicated that the Cu concentration was extremely low (≤0.015 mg/L), while Cd was not detected in the overlying water or the interstitial water after the 90-day BC treatment. The pH value (7.5–8.1) slightly increased, and the toxicity characteristic leaching procedure (TCLP) leachability of the Cu and Cd in the sediment decreased overall. Cu and Cd were preferentially transformed into more stable species. The findings highlighted the potential possibility of BC derived from post-adsorbent being used for sediment remediation. However, the BC addition produced significant effects on the sediment microbial activity and community structure. In general, with an increase in BC, the urease activity increased, while the alkaline phosphatase and invertase activity decreased, which could be attributed to the BC itself. In addition, significant changes in both bacterial and fungal genera were observed. Hence, a cautious approach should be taken in the practical application of BC.